مقصد الحرية في الاسلام دراسة مقارنة بالقانون الوضعي - صالح، عبد الهادي احمد محمد
One of the characteristics of Islam is that it is a comprehensive religion for all aspects of life, as it is a complete religion that does not need to be increased by anyone. All Muslims realized that. The problem: that some Muslims did not realize that, so they were affected by the West. They started requisition for the application of all that the West believes in and the slogans it raises. The most important slogans chanted by them is "freedom". They elaimed ignorantly that the West was the first who brought the freedom and the Islam did not bring the freedom and did not concern about it. In addition, they claimed that there is no explicit utterance calling for freedom in Islam, as it is clear and explicit in the Universal Declaration of Human Rights. Research objectives: The most important objective is proving the validity of Islamic legislation for every time and place. Definition of legislative law and proving that it is a man-made, therefore it is imperfect, regardless of the mind of its authors. To explain freedom, define it, and state its rank in Islam. A statement that Islam has decided the principle of freedom and made it a basic goal that it seeks to achieve. Besides, the Islam has preceded other legislation as well as decided it in the most magnificent way. Methodology: The study followed the inductive approach by collecting all the texts mentioned in the topic, then editing, revising and verifying their original sources. Then the analytical method reveal the legislative laws mentioned in the topic. Additionally, the study mentioned Islamic legislation and interpreted how it is distinguished from others, as well as the comparative approach in order to prove the validity of Islamic legislation for every and place. Findings: Throughout the research we have found that Islamic legislation is valid for every time and place with evidence that the first emergence of freedom in Islam is by the mission of the Prophet Mohammed, peace and blessings be upon him, in the sixth century AD, while the first prominent emergence of the term freedom in Western thought and legislative laws was at the beginning of the seventeenth century AD, or a little earlier. The researcher concluded that Islam considered freedom an important destination, the application of all intents depends on its existence or absence, and that Islam decided the principle of freedom and clarified it more clearly than the Universal Declaration of Human Rights. Conclusion: The research concluded that Islam preceded others for centuries in determining freedom, and when freedom decided to grant it to all people, it did not grant it to them with a claim from them. Rather, it granted them originality as human beings, while freedom in the West did not come until after great demands and massive revolutions that continued for many years. Finally, freedom in Islam is guaranteed to all people, Muslim and infidel the same.